Improvement in 100-m Sprint Performance at an Altitude of 2250 m - Nicholas P. Linthorne (MDPI AG, 2016)
A fair system of recognizing records in athletics should consider the influence of environmental conditions on performance. The aim of this study was to determine the effect of an altitude of 2250 m on the time for a 100-m sprint. Competition results from the 13 Olympic Games between 1964 and 2012 were corrected for the effects of wind and de-trended for the historical improvement in performance. The time advantage due to competing at an altitude of 2250 m was calculated from the difference between the mean race time at the 1968 Olympic Games in Mexico City and the mean race times at the low-altitude competition venues. The observed time advantage of Mexico City was 0.19 (±0.02) s for men and 0.21 (±0.05) s for women (±90% confidence interval). These results indicate that 100-m sprinters derive a substantial performance advantage when competing at a high-altitude venue and that an altitude of 1000 m provides an advantage equivalent to a 2 m/s assisting wind (0.10 s). Therefore, the altitude of the competition venue as well as the wind speed during the race should be considered when recognizing record performances.